Perempuan Dan Budaya Batak: Feminisme Dalam Dalihan Na Tolu Masyarakat Batak Angkola - Rambe, Yasir Maulana; Muhammad Adika Nugraha (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
Dalihan Na Tolu is a social system system found in the Angkola Batak Community. Dalihan Na Tolu regulates the social interaction of the Batak Angkola community as a whole. The objectives of this study are (1) how is the position and role of Dalihan Na Tolu in regulating the social and cultural system of the Batak Angkola community, (2) how is the role and position of women in the social system of Dalihan Na Tolu Batak Angkola, (3) how is the concept of gender differences in Batak Angkola culture, and (4) how is the role of women in the social, political, economic fields of the Batak Angkola community. The research used a qualitative method with an ethnomethodological approach. For the Batak Angkola community, Dalihan Na Tolu has a strong and binding role in social life. Women in the Dalihan Na Tolu social system are incarnated not only as individuals, but as an element of Dalihan Na Tolu called Anak Boru. The Angkola Batak community places men in the public sphere while women tend to take care of the internal sphere.